Relationship Analysis of Teacher’s Pedagogic Competence and Social Competence in Using the Disability Friendly School (DFS) Model to the Quality of Learning in the Inclusion Early Childhood SKB Kota Pekanbaru - Novianti, Ria; Mahardhani, Ardhana Januar; Alvi, Ria Rizkia; Wulansari, Betty Yulia; Aziza, Rizqia Putri (PPSDP International Journal of Education, 2023)
The purpose of this study was to determine the relationship between pedagogic competence and social competence of teachers in using the Disability Friendly School Model on the Learning Quality of the Inclusion Early Childhood SKB Kota Pekanbaru. The method used is a quantitative method. The data collection technique was carried out using a questionnaire. The results of the questionnaire were then analyzed using correlation nonparametric analysis to determine the positive and significant relationship between variables. The main finding of this study (1) Pedagogic Competence does not have a positive and significant relationship to the Quality of Learning, (2) Social Competence has a positive and significant relationship to the Learning Quality, (3) Pedagogic Competence and Social Competence have a positive and significant relationship to the Learning Quality of The Inclusive Early Childhood of SKB Kota Pekanbaru. Novelty of this study This is the first study used to test the DFS Model teachers at SKB Pekanbaru City. DFS is an alternative model of child-friendly schools for children with disabilities that have been developed since 2022.